Prevalence and Risk Factors Associated with Type 2 Diabetes in Elderly Patients Aged 45-80 Years at Kanungu District - Debrah Asiimwe; Godfrey O. Mauti; Ritah Kiconco (Journal of Diabetes Research)
Background. Type 2 diabetes is a worldwide disaster including in Uganda, specifically in Kanungu District which had a rise in diabetic patients in 2018/2019 as compared to the 2017/2018 financial year. This research was determined to access the prevalence and risk factors associated with type 2 diabetes on elderly patients aged 45-80 years attending Kanungu Health Centre IV, Kanungu District. Methods. A cross-sectional study was conducted among patients aged 45-80 years attending Kanungu Health Centre IV from June to August 2019. The prevalence of type 2 diabetes was determined by the blood sugar of patients. Questionnaires were used to collect data for factors associated with type 2 diabetes. Data were statistically analyzed using the statistical package for social sciences (SPSS) version 25 (SPSS Inc., USA) at P<0.05. Results. The overall prevalence of type 2 diabetes was 18.7% among the tested patients. 22.8% of diabetic patients were females as 7.8% were males. The age group most affected by diabetes was 61-65 years. Alcoholism, smoking, body mass index (BMI), and family history were found to be significantly associated with type 2 diabetes at P value < 0.05. Conclusion. There was a high prevalence of type 2 diabetes observed in this study compared to studies done in previous years which raise a public health concern. This study also found that females and patients aged 61-65 years were most affected by diabetes. Lastly, the presence of family history for diabetes, overweight, and being obese increases the chances of acquiring type 2 diabetes.